Global Mapping of Protein–Lipid Interactions by Using Modified Choline‐Containing Phospholipids Metabolically Synthesized in Live Cells - Wang, Danyang; Du, Shubo; Cazenave‐Gassiot, Amaury; Ge, Jingyan; Lee, Jun‐Seok; Wenk, Markus R.; Yao, Shao Q. (Angewandte Chemie International Edition, 2017)
The protein–lipid interaction is an essential metabolic process that mediates cellular signaling and functions. Existing strategies for large‐scale mapping studies of the protein–lipid interaction fall short in their incompatibility with metabolic incorporation or inability to remove unwanted interferences from lipidated proteins. By incorporating an alkyne‐containing choline head group and a diazirine‐modified fatty acid simultaneously into choline‐containing phospholipids synthesized from live mammalian cells, protein–phospholipid interactions have been successfully imaged in live cells. Subsequent in situ profiling of the modified Cho phospholipid‐crosslinked proteins followed by quantitative proteomics allowed identification of several hundred putative phospholipid‐interacting proteins, some of which were further validated. Double the load: A novel double incorporation strategy for metabolic biosynthesis of bifunctional choline‐containing phospholipids (for example phosphatidylcholine (PC); see picture) was developed. This strategy offers significant improvement for global mapping of genuine protein–lipid interactions from live mammalian cells.